Candidate Population III stellar complex at z = 6.629 in the MUSE Deep Lensed Field. (13th March 2020) - Vanzella, E; Meneghetti, M; Caminha, G B; Castellano, M; Calura, F; Rosati, P; Grillo, C; Dijkstra, M; Gronke, M; Sani, E; Mercurio, A; Tozzi, P; et al.
ABSTRACT: We discovered a strongly lensed (μ ≳ 40) Ly α emission at z = 6.629 (S/N ≃ 18) in the MUSE Deep Lensed Field (MDLF) targeting the Hubble Frontier Field (HFF) galaxy cluster MACS J0416. Dedicated lensing simulations imply that the Ly α emitting region necessarily crosses the caustic. The arc-like shape of the Ly α extends 3 arcsec on the observed plane and is the result of two merged multiple images, each one with a de-lensed Ly α luminosity L ≲ 2.8 × 10 40 erg s −1 arising from a confined region (≲150 pc effective radius). A spatially unresolved Hubble Space Telescope ( HST ) counterpart is barely detected at S/N ≃ 2 after stacking the near-infrared bands, corresponding to an observed (intrinsic) magnitude m 1500 ≳ 30.8 (≳35.0). The inferred rest-frame Ly α equivalent width is EW0 > 1120 Å if the IGM transmission is T IGM < 0.5. The low luminosities and the extremely large Ly α EW0 match the case of a Population III (Pop III) star complex made of several dozens stars (∼10 4 M⊙ ) that irradiate an H ii region crossing the caustic. While the Ly α and stellar continuum are among the faintest ever observed at this redshift, the continuum and the Ly α emissions could be affected by differential magnification, possibly biasing the EW0 estimate. The aforementioned tentative HST detection tends to favour a large EW0, making such a faint Pop III candidate a key target for the James Webb Space Telescope and Extremely Large Telescopes.